The behaviour of kinematic parameters during a time to exhaustion test at VO2max in elite swimmers - Marinho, D. A.; Vilas-Boas, J. P.; Keskinen, K. L.; Rodriguez, F. A.; Soares, S. M.; Carmo, C. M.; Vilar, S. O.; Fernandes, R. J. (Journal of Human Movement Studies, 2006)
The aim of this study was to analyse, in swimming pool conditions, the behaviour of kinematic parameters - stroke rate (SR), stroke length (SL) and stroke Index (SI) - during a time to exhaustion test performed at the minimum velocity that elicits maximal oxygen uptake (TLim-vVO2max) in elite freestyle swimmers. Eleven svvimmers from the National Portuguese Swimming Team (five male and six female) performed an intermittent incremental test for vVO2max assessment and an all-out swim at vVO2max to determine TLim-vVO2max and to analyse the evolution of the kinematic parameters throughout the test. SR increased and SL (and SI) decreased during the TLim-vVO2max test, as a general tendency. When the differences in SR, SL and SI between each 12.5% section of the test were tested, a significant increase in SR and a decrease in SL and SI was verified at 25% [(74.00 (25.83m)], 50% [(148.10 (51.66m)] and 87.5% [(259.15 (90.41m)] of theTLim-vVO2max duration. These data showed a reduction of the propelling efficiency throughout such a test. These findings could be useful when designing training programmes, namely of middle distance swimmers, taking into consideration maximum aerobic speed, time to exhaustion and propelling efficiency.